Prescription Requirements and Patient Autonomy: Considering an Over-the-Counter Default - Kilbride, Madison (The Hastings Center report, 2020)
When new drugs are approved by the Food and Drug Administration, the default assumption is that they will be available by prescription only, safe for use exclusively under clinical supervision. The paternalism underlying this default must be interrogated in order to ensure appropriate respect for patient autonomy. Upon closer inspection, prescription requirements are justified when nonprescription status would risk harm to third parties and when a large segment of the population would struggle to exercise their autonomy in using a drug safely and effectively on their own. Although these justifications can support prescription status for many drugs, we propose that reversing the FDA's current default to instead begin with a presumption in favor of over-the-counter status is the best way to avoid interference with valid claims of patient autonomy. Under this approach, a range of drug products could be considered for an OTC switch, including oral contraceptives, statins, and HIV-prevention drugs.